Dark and singular soliton solutions of perturbed Gerdjikov-Ivanov equation via the first integral method - Subhaschandra Singh, Salam (International Journal of Physical Research, 2018)
This paper employs the first integral method in obtaining dark and singular soliton solutions of perturbed Gerdjikov-Ivanov equation showing that the method is a powerful tool for finding exact solutions of many nonlinear evolution (NLE) equations which are found in the studies of social dynamics, nonlinear science and engineering.Â Â